Stakeholder Relations Travelkif dengan KBRI Paris dalam Business Sustainability - Akbar, Dinul Fajri; Sari, Juwita Permata; Wempi, J.A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The COVID-10 pandemic has created a contraction for the tourism industry in Indonesia due to strict social mobility restrictions (lockdown) in all regions. Thus, travel service business actors are affected and must be able to survive the uncertainty of the situation. Maintaining business sustainability cannot be separated from the role of stakeholders, such as that carried out by TravelKif. Through a dynamic strategic approach, TravelKif strives to proactively build and maintain its relationship with the Indonesian Embassy in Paris for business sustainability through its involvement in collaborative activities and personal strategic initiatives. This research aims to identify the implementation of stakeholder strategies carried out by TravelKif in building and maintaining its relationship with the Indonesian Embassy in Paris to maintain business sustainability. The research method used is qualitative with a descriptive approach. The results of this study indicate that the stakeholder relationship strategy carried out by TravelKif towards the Indonesian Embassy in Paris can make TravelKif's business sustainability survive, grow, and develop positively. Through the Indonesian Embassy in Paris role, TravelKif can obtain new clients from its partner networks and highlights from its publications. The implications of stakeholder relations on TravelKif's business sustainability can make it easier for companies to escape from difficult situations, increase stakeholder trust, and improve more solid relationship interactions.